Ab initia Geometry-Optimization and NMR Studies of Chemical Constituents of Piper sarmentosum - I, Noorbatcha; S, Hassan; A. Hadi, Hamid; Awang, Khalijah (Malaysian Journal of Science, 2002)
The structures of two compounds, γ-asarone (1-ally1-2,4,5-trimethoxybenzene) $1$ and asarylaldehyde (2,4,5-trimethoxybenzaldehyde) $2$ from $Piper$ $sarmentosum$, locally known as ‘kaduk’, have been studied by HNMR, CNMR spectroscopy and quantum chemical calculations. The NMR shifts are calculated using Hartree Fock (HF) and Density Functional Theory (DFT) methods. We find that the $ab$ $initio$ calculations are very useful in assigning the NMR peaks and provide insights on the electronic factors affecting the NMR shifts.